2018
DOI: 10.1002/slct.201801692
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of NbSe2 Flakes as Reversible Host Materials for Sodium‐Ion and Potassium‐Ion Batteries

Abstract: Transition metal dichalcogenides have captured much attention in recent years. NbSe2, as one of transition metal dichalcogenides, has been explored as electrode materials for sodium‐ion and potassium‐ion batteries and delivered a high reversible electrochemical performance. Flakes NbSe2 electrode materials deliver a discharge capacity of 115 mA h g‐1 for sodium‐Ions batteries and 95 mA h g‐1 at 25 mA g‐1 for potassium‐Ions batteries in the first cycle respectively, with high coulomb efficiency. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The NbSe 2 flake electrode has ad ischarge capacity of 115mAh g À1 ,a nd the capacity retention is 91 %f rom the 2nd to the 50th cycle ( Figure 17 C). [177] Ex situ XRD measurementss how that NbSe 2 ,N a 0.5 NbSe 2 ,a nd NaNbSe 2 retain the same P63/mmc space group duringN a + intercalation, indicating that NbSe 2 possesses af avorable host structure for Na + storage. [17] Layered VS 2 has an intrinsic metallic conductivity with large interlayer distances (5.76 ).…”
Section: D Tmds For Sibsmentioning
confidence: 93%
See 2 more Smart Citations
“…The NbSe 2 flake electrode has ad ischarge capacity of 115mAh g À1 ,a nd the capacity retention is 91 %f rom the 2nd to the 50th cycle ( Figure 17 C). [177] Ex situ XRD measurementss how that NbSe 2 ,N a 0.5 NbSe 2 ,a nd NaNbSe 2 retain the same P63/mmc space group duringN a + intercalation, indicating that NbSe 2 possesses af avorable host structure for Na + storage. [17] Layered VS 2 has an intrinsic metallic conductivity with large interlayer distances (5.76 ).…”
Section: D Tmds For Sibsmentioning
confidence: 93%
“…The NbSe 2 sample shows excellent cycling stability and rate performance for Na storagew ith an initial reversible capacity of 116.6 mAh g À1 and retained capacity of 98.1 mAh g À1 after 100 cycles at 100 mA g À1 . [176] Moreover,acapacity of 78.6 mAh g À1 was observed at ah igh current density of 4000 mA g À1 ,s uggesting excellent rate capability.L uo et al [177] demonstrated that NbSe 2 has aclosed hexagonal and layered structure, in which each Nb atomic layer is sandwiched between two Se atomicl ayers and bonded by van der Waals forces betweent he layers (Figure 17 A). Thea s-synthesized layered NbSe 2 has an almost regularh exagon morphology with a thickness of 500 nm.…”
Section: D Tmds For Sibsmentioning
confidence: 99%
See 1 more Smart Citation
“…During charging, K + can form K y X, and in the meantime the transition metal elements are reduced to zero valence. [39][40][41][42][43][44] Typical conversion anode materials encompass transition metal oxides (…”
Section: Potassium-ion Storage Mechanismmentioning
confidence: 99%
“…Anode candidates belonging to conversion type are usually transition metal compounds (TM a X b , TM: transition metal; X: O, S, F, P, N). During charging, K + can form K y X, and in the meantime the transition metal elements are reduced to zero valence 39‐44 . Typical conversion anode materials encompass transition metal oxides (Co 3 O 4 , Fe 2 O 3 ), 45,46 transition metal chalcogenides (MoS 2 , MoSe 2 ), 47,48 transition metal nitrides (VN, Fe 2 N), 49 and transition metal phosphides (CoP, MoP) 50,51 .…”
Section: Potassium‐ion Storage Mechanismmentioning
confidence: 99%